Digital Health Education for Teen Girls: The Effectiveness of Video Media in Enhancing Knowledge on Iron Deficiency Anemia Prevention : Edukasi Kesehatan Digital untuk Remaja Perempuan: Efektivitas Media Video dalam Meningkatkan Pengetahuan tentang Pencegahan Anemia Defisiensi Besi - Salsabila Salsabila; Baharuddin Condeng; Selvi Alfrida Mangundap; Fitria Masulili; Ismunandar Ismunandar (Poltekkes Kemenkes Palu, 2025)
Background: Anemia remains a global health problem, especially among adolescent girls who are prone to iron deficiency due to increased needs during growth. Lack of knowledge about anemia prevention contributes to the high prevalence of this condition. Research Objective: To analyze the effect of health education using video media on adolescent girls' knowledge about anemia prevention. Methods: A quantitative study with a one-group pretest–posttest quasi-experimental design was conducted on 36 female students in grade XI at SMA Negeri 1 Sindue, selected through purposive sampling. Data were obtained using knowledge questionnaires before and after the intervention, then analyzed using the Wilcoxon signed rank test at a significance level of 0.05. Results: The study showed that the average knowledge score before the intervention was 10.47 (SD 1.682) with a range of 6–14, while after the intervention it increased to 14.83 (SD 0.378) with a range of 14–15. The statistical test produced a p-value <0.001, indicating a significant difference between the knowledge scores before and after the intervention. Conclusion: These findings indicate that video-based health education is effective in improving adolescent girls' knowledge about anemia prevention.